Problem gambling and psychological distress: a cross-national perspective on the mediating effect of consumer debt and debt problems among emerging adults - Atte Oksanen; Iina Savolainen; Anu Sirola; Markus Kaakinen (BMC, 2018)
Abstract Background Severe economic difficulties are common among younger generations who currently have an easy access to consumer credit and payday loans in many Western countries. These accessible yet expensive short-term loans may lead to more severe financial difficulties, including default and debt enforcement, both which are defined as debt problems within this study. This study hypothesized that consumer debt and debt problems mediate the relationship between problematic gambling and psychological distress. Excessive gambling can be funded with consumer debt, which in turn leads to the accumulation of financial stressors and, eventually, psychological distress. Methods Three studies were conducted to examine the hypotheses. Study 1 used a demographically balanced sample of Finnish participants aged 18 to 25 years (n = 985, 50.76% female). Study 2 used a sample collected from Finnish discussion forums and social networking sites, with participants ranging from 18 to 29 years of age (n = 205, 54.63% female). Study 3 used a demographically balanced sample of American youths aged 18 to 25 years (n = 883, 50.17% female). Analyses were based on generalized structural equation models examining the role of problem gambling, consumer debt, and debt problems (i.e., default and debt enforcement) on psychological distress. Additional mediation analysis was run with treating both instant loans and debt problems as mediators. Results All three studies showed that problem gambling was associated with consumer debt, which was further associated with debt problems. Both consumer debt (studies 1 and 2) and debt problems (study 3) were associated with psychological distress. Problem gambling was also directly associated with psychological distress in studies 1 and 3, but not in study 2. In Finland, consumer debt mediated the relationship between problem gambling and psychological distress (studies 1 and 2), while study 3 underlined the mediating role of debt problems in the USA, where consumer debt itself was not positively associated with psychological distress. Conclusions The results of the three studies indicate that problem gambling-related psychological distress is partly explained by consumer debt. Consumer credit and payday loans may provide resources for gamblers that enable them to keep up with the habit. This may eventually lead to debt problems and psychological distress. Cross-national differences exist, but in both Nordic and American models, similar mechanisms prevail. The results imply that limiting consumer debt among emerging adults could cushion the financial and psychological costs of problem gambling.